2015
DOI: 10.1017/s1047951115000359
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous sildenafil in children with palliated single ventricle heart defects: effect of elevated hepatic pressures

Abstract: Aims Sildenafil is frequently prescribed to children with single ventricle heart defects. These children have unique hepatic physiology with elevated hepatic pressures which may alter drug pharmacokinetics. We sought to determine the impact of hepatic pressure on sildenafil pharmacokinetics in children with single ventricle heart defects. Methods A population pharmacokinetic model was developed using data from 20 single ventricle children receiving single dose intravenous sildenafil during cardiac catheteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…20 Many studies have shown that the usage of drugs has certain impact on congenital heart disease, such as anti-infective drugs, sulfonamides have significant impact on the normal development of cardiovascular system, but the relationship between penicillin and congenital heart disease is not certain. 21,22 Antiasthma, antidepressant, antifungal drugs and drugs for treating hypertension and hypothyroidism all increased the incidence of congenital heart disease. 23 Several large-scale studies have shown that pregnant women who took progesterone, amphetamine, anticancer drugs and methionine in the early pregnancy significantly increased the risk of developing CHD in their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…20 Many studies have shown that the usage of drugs has certain impact on congenital heart disease, such as anti-infective drugs, sulfonamides have significant impact on the normal development of cardiovascular system, but the relationship between penicillin and congenital heart disease is not certain. 21,22 Antiasthma, antidepressant, antifungal drugs and drugs for treating hypertension and hypothyroidism all increased the incidence of congenital heart disease. 23 Several large-scale studies have shown that pregnant women who took progesterone, amphetamine, anticancer drugs and methionine in the early pregnancy significantly increased the risk of developing CHD in their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…In the first days of neonatal life, the clearance of sildenafil is about one-third of that seen in adults with increased half-life of 48-56 hours. This could be explained by immaturity of the cytochrome P450 system, which becomes mature in the first week of life [10].…”
Section: Discussionmentioning
confidence: 99%
“…Since children with single ventricle heart defects have altered hepatic physiology that might influence drug metabolism, a study was conducted to determine the effect of elevated hepatic pressure on the pharmacokinetics (PK) of sildenafil in this population [11]. A population PK model was developed for 20 children with a median (range) age of 3.2 years (0.8–5.3) receiving single dose intravenous sildenafil during cardiac catheterization.…”
Section: Cardiologymentioning
confidence: 99%
“…Additionally, predicted drug exposure increased in subjects with hepatic pressures ≥10 mmHg compared to <10 mmHg by approximately 1.5 fold (median area under the concentration versus time curve, 533 vs. 792 ug·h/L). As such, the investigators concluded that hepatic pressure should be considered when prescribing sildenafil for children with single ventricular defects [11]. …”
Section: Cardiologymentioning
confidence: 99%